A study on the absorption of ammonia into water in a rotor‐stator reactor. (31st October 2014) - Li, Yingwen; Sun, Baochang; Zeng, Zequan; Song, Yunhua; Chen, Jianming; Chu, Guangwen; Chen, Jianfeng; Shao, Lei
<x xml:space="preserve">Abstract</x> This article presents experimental and modelling studies on the absorption of NH3 into water in a rotor‐stator reactor (RSR). The influences of operating parameters such as the rotation speed of rotor, liquid flow rate, and gas flow rate on the overall volumetric mass transfer coefficient (Kya) of NH3 were investigated. It was found that Kya increased with an increasing rotation speed, liquid flow rate, and gas flow rate. A correlation to predict the Kya of NH3 in the RSR was established and found to be in agreement with the experimental data with deviations within 10 %. A comparison was made between the Kya of NH3 in the RSR and RPB, and the result showed that Kya of NH3 in the RSR was 13 % higher than that in the RPB, thus signifying that the RSR has better intensification effect for mass transfer limited processes than the RPB.